PENGARUH PERBANDINGAN TEPUNG BERAS HITAM (Oryza sativa L. indica) DENGAN TERIGU TERHADAP KARAKTERISTIK BAKPAO - Hidayat, Rizky Rahmat; Sugitha, I Made; Wiadnyani, Anak Agung Istri Sri (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 8 No 2 (2019): Jurnal ITEPA, 2019)
The purpose of study was to find the optimum ratio of black rice flour (Oryza sativa L. indica) with wheat to produce bakpao with the best characteristics. The Randomized Block Design (RBD) was used in the research with treatment that is the ratio of black rice flour with wheat which consist of 6 levels: 0%:100%, 5%:95%, 10%:90%, 15%:85%, 20%:80%, 25%:75%. The treatment was repeated 3 times to obtain 18 units of experiment. The data obtained were analyzed by variance and if the treatment had an effect on the observed variable then continued with Duncan Multiple Range Test (DMRT) test. The ratio of black rice flour to wheat had significant effect to protein content, fat content, IC50, texture, color (hedonic and scoring), texture (hedonic), taste (scoring) and overall acceptance (hedonic). Not Significant effect to moisture content, ash content, carbohydrate content, crude fiber content, texture (scoring) and taste (hedonic). The ratio of black rice flour and wheat  (10%:90%) produces bakpao with the best characteristics namely: 37.44% moisture content, 0.85% ash content, 7.46% protein content, 6.10% fat content, 48.15% carbohydrate content, 2.42% crude fiber content, swelling power 52.41%, IC 50 41,48 g/100g, texture 9.87 N/mm, grey color, rather soft texture, tasted rather like black rice, rather liked color and flavor, liked texture, taste and overall acceptability.